Prevalence of dry socket following extraction of permanent teeth at Kathmandu University Teaching Hospital (KUTH), Dhulikhel, Kavre, Nepal: A study - Upadhyaya, C; Humagain, M (Kathmandu University Medical Journal, 2010)
Background: One of the most common postoperative complications following the extraction of permanent teeth is a condition known as dry socket. Although the aetiology of dry socket is debated, it is probably multifactoral, and its pathogenesis remains unknown. Objectives: The aim of the study was to evaluate incidence of dry socket following extraction of permanent teeth at dental out-patient department (OPD) of Dhulikhel hospital, Kathmandu university teaching hospital (KUTH), Kavre, Nepal. Materials and methods: Retrospective reviews of records of total 1860 no of patients were studied who underwent extraction of permanent teeth for various reasons since January 2007 to December 2008 period. There were 873(47%) male patients and 987(53%) female patients. Information regarding indications for extraction, extracted tooth status, onset of symptoms, relevant findings of the examining clinician, interval between presentation, management given, and its outcome were retrieved and analysed. Results: A total 1860 no of patients were studied who underwent extraction of total 2640 number of permanent teeth for various reasons. A total of 103 (3.9%) extractions were complicated by dry socket in patients aged 11 to 80 years with female predominance (54.4%). Conclusion: The etiology of dry socket is multifactorial and ultimately it is the host's healing potential which determines the severity and duration of the condition. The incidence of dry socket was found as 3.9% in this study. The incidence was higher in female patients (54.4%) and in mandibular teeth extraction cases (68.93%). Key words: Extraction; Dry socket; Teeth DOI: 10.3126/kumj.v8i1.3216 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 18-24